Vitamin A Update: Forms, Sources, Kinetics, Detection, Function, Deficiency, Therapeutic Use and Toxicity - Carazo, Alejandro; Macáková, Kateřina; Matoušová, Kateřina; Krčmová, Lenka Kujovská; Protti, Michele; Mladěnka, Přemysl (Nutrients, 2021)
Vitamin A is a group of vital micronutrients widely present in the human diet. Animal-based products are a rich source of the retinyl ester form of the vitamin, while vegetables and fruits contain carotenoids, most of which are provitamin A. Vitamin A plays a key role in the correct functioning of multiple physiological functions. The human organism can metabolize natural forms of vitamin A and provitamin A into biologically active forms (retinol, retinal, retinoic acid), which interact with multiple molecular targets, including nuclear receptors, opsin in the retina and, according to the latest research, also some enzymes. In this review, we aim to provide a complex view on the present knowledge about vitamin A ranging from its sources through its physiological functions to consequences of its deficiency and metabolic fate up to possible pharmacological administration and potential toxicity. Current analytical methods used for its detection in real samples are included as well.
Keywords: fyziologie výživy; hypovitaminosis; retinol; Vitamin A Deficiency; gene regulation; retinoid receptor; Vitamin A; nedostatek vitaminu A; Nutritional Physiological Phenomena; lidé; vision; toxicity; Humans; cancer; vitamin A; retinoic acid